Potential Money Laundering Crimes Through Blockchain-Based Digital Legal Insurance Schemes In Indonesia - Necklina Druhandani; Adi Muhajirin (Dinasti Research, 2026)
Potential Money Laundering Crimes Through Blockchain-Based Digital Legal Insurance Schemes In Indonesia. The background issue is the rapid growth of digital insurance vulnerable to financial crime due to blockchain anonymity features. The objectives are to determine the mechanism of digital legal insurance schemes, analyze money laundering potential, and examine criminal law regulations in Indonesia. The research method uses normative juridical with statute and conceptual approaches. The results show that blockchain anonymity and smart contracts create loopholes for placement, layering, and integration stages of illegal funds. Current regulations do not specifically regulate risk mitigation in legal insurtech products. The conclusion suggests revising the money laundering prevention law and stricter financial services authority supervision. Stricter identity verification is required on digital legal insurance platforms and including this product in the suspicious transaction reporting list to prevent misuse of the legal insurance system as a means of money laundering that can hinder the criminal justice process